Patterns and Determinants of Price Changes: Analysing Individual Consumer Prices in Austria - Josef Baumgartner; Ernst Glatzer; Fabio Rumler; Alfred Stiglbauer (Austrian Institute of Economic Research (WIFO), 2006)
We provide empirical evidence on the degree and characteristics of price rigidity in Austria by estimating the average frequency of price changes and the duration of price spells from a large data set of individual price records collected for the computation of the Austrian CPI.
Keywords: 330; Consumer prices; sticky prices; frequency and size of price changes; duration of price spells; Verbraucherpreisindex; Preisrigidität; Schätzung; Österreich